Investigating the Leadership Styles and National Culture of Emirati Female School Principals - Al Khatib, Soulafa (2019)
Background: With the growing expectations from the field of education day by day, increases the importance of effective school leadership. Leadership is the procedure through which the leaders can influence the decision making process and set the goals of the institution. They apply their influence over other behaviors in order to achieve the set goals. The school proves its effectiveness depending on various factors; the principal’s leadership style is the main one. Purpose: The purpose of this study was to investigate the influence of the female gender and national culture dimensions on the leadership styles of the Emirati female school principals, as educational leaders, and the relationships that exist among the different variables. Design/ Methodology/ Approach: The researcher employed Explanatory Sequential mixed method approach in two phases for this study. In the first phase, the quantitative data was collected using the MLQ (5X-short) survey and the cultural dimensions survey. In the second phase, the researcher conducted semi-structured interviews and qualitative observations. Results: the findings of the study indicated that the Emirati female leaders tend to be more transformational in their leadership styles while they still practice transactional leadership to a certain degree. The female principals were found to be more “androgynous” carrying the qualities of both male and female leaders. In addition, the leadership styles and their elements proved to have significant relationship to national culture dimensions except for management by exception (active) that has no significant correlation with any of the culture dimensions. Research Limitations & Implications: Future research should include a larger sample size and the perspectives of the followers as well. It is important to conduct the study in different organizational context not only in schools to confirm the finding that women use “androgynous” style in the UAE and beyond. Some recommendations were also provided to principals and policy makers to design and implement policies and professional development for effective leadership, taking into consideration the UAE cultural dimensions